Nanoemulsion preparation by combining high pressure homogenization and high power ultrasound at low energy densities. (May 2016) - Calligaris, Sonia; Plazzotta, Stella; Bot, Francesca; Grasselli, Silvia; Malchiodi, Annalisa; Anese, Monica
Abstract: Combinations of high pressure homogenization (HPH) and ultrasound (US) were studied as alternative processes to individual HPH and US to produce stable nanoemulsions, while reducing the energy requirement. A 15% ( w / w ) oil-in-water mixture containing 4.5% ( w / w ) of a blend of Tween 80 and Span 80 (1:1 w / w ) was homogenized by means of combinations of HPH and US. In particular, 20 to 100 MPa HPH was applied before or after 20 or 60 s US, providing low and medium energy densities. Emulsions were analyzed for particle size distribution and mean diameter, viscosity and physical stability. Results were compared with those relevant to emulsions prepared by the application of individual HPH and US, providing comparable or higher energy densities. US and HPH applied in combination at low and medium energy density values allowed to obtain nanoemulsion having lower mean particle dimensions and, in most cases, higher stability than those prepared by using individual US or HPH at high energy densities. A greater efficiency was found for US preceding HPH. Highlights: Combinations of HPH and US at low-medium energy input allowed obtaining nanoemulsions. The greatest efficiency was found for US preceding HPH. Combined US-HPH allowed up to 6 times energy reduction